Cannabinoid receptor type‐1 and its correlation with CB1 gene polymorphism‐1359G/A in ectopic pregnancy compared to the control group - Moudi, Bita; Heidari, Zahra; Asemi‐Rad, Azam; Mahmoudzadeh‐Sagheb, Hamidreza; Sheibak, Nadia; Ghasemi, Marzieh; Eslami, Sanaz (The journal of obstetrics and gynaecology research, 2021)
Aim Ectopic pregnancy (EP) is one of the most important causes of maternal mortality. This study aimed to evaluate the immunohistochemical (IHC) expression of the cannabinoid receptor type‐1 (CB1) and its association with CB1‐1359G/A gene polymorphism (rs1049353) in the fallopian tubes in EP compared to controls. Methods In this case–control study, 100 women with EP (cases) and 100 women that underwent abdominal surgery due to the hysterectomy or uterine tubal ligation (healthy controls) were included. Genotyping of CB1‐1359G/A polymorphism, tissue expression of CB1 at the protein and mRNA levels were studied using restriction fragment length polymorphism, IHC method, and quantitative real‐time polymerase chain reaction (qRT‐PCR) analysis. Results Genotyping showed that in EP, the frequency of AA, AA+AG genotypes, and A allele was significantly higher than healthy control subjects (p = 0.001). Also, patients with EP had significantly increased IHC expression of CB‐1 compared to the control samples (p = 0.016). Patients with AA and AG genotypes had a significantly higher IHC expression of CB‐1 compared to the GG genotype. qRT‐PCR analysis showed that patients with EP had significantly increased expression of CB‐1 compared to the control samples (p < 0.001). Patients with AA and AG genotypes had higher significant mRNA expression of CB‐1 compared to the GG genotype. Conclusions CB1 is likely to be effective in creating innate immunity in humans and can affect the process of EP in the fallopian tube. CB1 is also a pathological valuable factor in identifying the pathway of inflammation during ectopic implantation.